A novel break site of EML4‐ALK report and a rare PRKAR1A‐ALK report analyzed by different ALK detection platforms in non‐small cell lung cancer patients. Issue 20 (6th September 2021) - Du, Xue; Zhang, Jun; Gao, Hongjun; Tai, Yanhong
Abstract: Background: detection of anaplastic lymphoma receptor tyrosine kinase gene (ALK) rearrangements in patients with non‐small‐cell lung cancer (NSCLC) has become a routine pathological diagnosis worldwide. Methods: there are three major conventional diagnostic methods for ALK fusions: fluorescent in situ hybridization (FISH); immunohistochemistry (Ventana IHC (D5F3)); and polymerase chain reaction (PCR). Next‐generation sequencing (NGS) technology as is a new tool for ALK status detection with great potential. These four methods are highly consistent in detecting ALK status (coincidence rate >96%). However, discrepancies in ALK status have been found in some patients among these methods, which causes confusion for clinicians. Results and conclusion: in this study, we analyzed two patients whose ALK statuses were not consistent using these four methods. We explored the potential reasons for deviation of the test results and found a novel EML4‐ALK break site, which had been not described previously. Abstract : This novel EML4‐ALK break site case is a typical example of a patient's clinical characteristics and pathologic findings indicating that the patient was ALK ‐positive. This result was confirmed by IHC and NGS. The patient responded well to the ALK inhibitor crizotinib after 1 month of treatment. In fact, the novel break site in this case is in exon 20 of ALK gene, which makes the kinase domain is not integral. This response indicated that even the ALK gene fusion domain is not structural integrity, the patient still could benefit from crizotinib. The disease progressed after 4 months of crizotinib treatment, which indicate that the missing of part exon 20 of ALK gene affect curative effect of crizotinib.